A case of acute liver failure due to hepatitis E virus, liver transplantation, and development of de novo autoimmune hepatitis. Issue 3 (23rd April 2020) - Choi, Jae Kyun; Ahn, Soomin; Cho, Jai Young; Choi, YoungRok; Han, Ho‐Seong; Jang, Boo‐ok; Choi, Gwang Hyeon; Jang, Eun Sun; Kim, Jin‐Wook; Jeong, Sook‐Hyang
Abstract: Acute hepatitis E virus (HEV) infection could lead to acute liver failure (ALF), which requires liver transplantation (LT). HEV infection could progress to chronic infection in an immunosuppressed host. De novo autoimmune hepatitis (AIH) is a rare occurrence of AIH during post‐LT immunosuppressive therapy in patients who underwent LT due to not AIH but some other etiology. Here, we report the first case of ALF due to HEV infection, the recurrence of HEV after LT that responded to ribavirin therapy, and then the development of de novo AIH showing a complete response to glucocorticoid therapy but multiple relapses after steroid withdrawal. This peculiar case suggests that HEV could have a pathogenic role in the development of the de novo AIH; additionally, this case report could help clinicians make therapeutic decisions in the post‐LT condition.